2011
DOI: 10.1038/mt.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided, Tumor Stroma-targeted 131I Therapy of Hepatocellular Cancer After Systemic Mesenchymal Stem Cell-mediated NIS Gene Delivery

Abstract: Due to its dual role as reporter and therapy gene, the sodium iodide symporter (NIS) allows noninvasive imaging of functional NIS expression by (123)I-scintigraphy or (124)I-PET imaging before the application of a therapeutic dose of (131)I. NIS expression provides a novel mechanism for the evaluation of mesenchymal stem cells (MSCs) as gene delivery vehicles for tumor therapy. In the current study, we stably transfected bone marrow-derived CD34(-) MSCs with NIS cDNA (NIS-MSC), which revealed high levels of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 46 publications
6
106
0
Order By: Relevance
“…However, depending on the approach used, MSCbased cancer gene therapy can include the destruction of exogenously applied engineered MSCs in the context of therapy, which is likely to overcome any endogenous tumour-promoting effects of adoptively applied MSCs. This was demonstrated in our previous work using MSCs as delivery vehicles for tumour-selective NIS gene delivery, showing no tumour growth-promoting effects in subcutaneous HuH7 or hepatic colon cancer metastasis xenograft mouse models where a significant therapeutic effect of 131 I or 188 Re was seen (Knoop et al 2011, Knoop et al 2013. Moreover, we did not observe an effect of thyroid hormone status or tetrac treatment on the growth of the HCC xenograft model used in this study, which we attribute to the absence of integrin avb3 on HuH7 cells and also to the short time frame for the assessment of tumour stroma-mediated effects on tumour growth in our experimental setting.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, depending on the approach used, MSCbased cancer gene therapy can include the destruction of exogenously applied engineered MSCs in the context of therapy, which is likely to overcome any endogenous tumour-promoting effects of adoptively applied MSCs. This was demonstrated in our previous work using MSCs as delivery vehicles for tumour-selective NIS gene delivery, showing no tumour growth-promoting effects in subcutaneous HuH7 or hepatic colon cancer metastasis xenograft mouse models where a significant therapeutic effect of 131 I or 188 Re was seen (Knoop et al 2011, Knoop et al 2013. Moreover, we did not observe an effect of thyroid hormone status or tetrac treatment on the growth of the HCC xenograft model used in this study, which we attribute to the absence of integrin avb3 on HuH7 cells and also to the short time frame for the assessment of tumour stroma-mediated effects on tumour growth in our experimental setting.…”
Section: Discussionmentioning
confidence: 91%
“…An array of growth factors, including PDGF, insulin-like growth factor 1 (IGF1), HGF, EGF and VEGF, as well as chemokines, such as RANTES/CCL5, CCL22 and, to a lower extent, SDF-1/CXCL12 and their respective receptors, have been implicated in MSC migration (Ponte et al 2007, Spaeth et al 2008) and many of these have been shown in this and other studies to be regulated by thyroid hormones via differential gene expression and receptor crosstalk (Davis et al 2011, Hercbergs et al 2012. Modulation of recruitment and engraftment efficiency of MSCs is of clinical interest, in settings of tissue regeneration, in the context of general tumour growth and the emerging field of MSC-based gene delivery in cancer therapy (Knoop et al 2011, Knoop et al 2013, Uchibori et al 2014. As the tumour stroma plays such a key role in tumour growth, angiogenesis and metastatic potential, it has become an important target for tumour therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human MSC do not develop into tumors [14], but some reports indicate that MSC participate in the pathogenesis of cancer by transforming into cancer-associated fibroblasts (CAFs) [15][16][17][18][19]. Some studies indicated that, when injected systemically, MSC migrate to sites of inflammation and diseased tissues [20][21][22][23]. The in vivo tropism toward gliomas has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%